The strategic defense initiative - Reiss, Edward (Cambridge studies in international relations, 1992)
This history of the Strategic Defense Initiative ranges across politics, economics, strategic studies and international relations, and provides the latest research into the SDI interest groups, the distribution of contracts, and the politics of influence. It discusses the wider contexts of 'Star Wars', such as alliance management, marketing, and domestic politics, and its military spin-offs, especially for anti-satellite (ASAT) and 'space control' programmes. The author tests the theoretical literature on the dynamics of the arms race by using SDI as a case study, and draws evidence from sources such as congressional hearings, interviews, the trade press, restricted briefing papers, and documents obtained under the US Freedom of Information Act. The book follows the fortunes of strategic defence into the changed global conditions of the 1990s, following the collapse of the Soviet bloc, the Gulf War, and President Bush's announcement of a refocused SDI, the Global Protection Against Limited Strikes (GPALS).